La Passione di Cristo in una sceneggiatura delle orgini di Frate Jacopone da Todi - Angelo Rella (Colloquia Theologica Ottoniana, 2014)
Undoubtedly Jacopone da Todi sacred representation Donna de Paradiso, a true inspired masterpiece, by reason of its writing seems to anticipate the modern theater script but especially the movie screenplay. We are convinced that Jacopone wrote Donna de Paradiso suggesting us a vision, persistently transforming the “literary language” into “visual language”. The writing of the Friar in our opinion contains the essence of the Seventh Art writing, it has the ‘visibility’ as first quality, and ‘action’ as its specifi city, it is that which Italo Calvino called “mental cinema”. Like the authors that after World War II staged the alienation of modern man, through his dialogues-monologues, reduced to a minimum, Jacopone show the anguish, loneliness and the inability to communicate of amother who is suffering for her own child. The audience-readers in the Middle Ages could not, and cannot today, do not be struck by the singular power of visual evocation of the passion, by the violent ‘embodied’ quality of its representation